Legal Categories in Intelligence Legislation: A Comparative Analysis - Proshchaiev, Volodymyr V. (International Journal of Criminology and Sociology, 2021)
The study employs the comparative legal method to investigate the features of the inclusion of legal categories reflecting intelligence activities as a specific social phenomenon in the laws on intelligence, as well as their interpretation by legislators from different countries. It has been found that in the legal regulation of intelligence activities there are general patterns inherent in the legislators of all countries. The study considers the features of application of the rules of legal technique in the legislation on intelligence through the investigation of issues of legal terminology, legal structures, and methods of constructing a law on an intelligence agency. The author proposes to conventionally divide all terms into three groups: common, used in everyday life; legal, with established and stable legal content and special, describing the special legal content and revealing the essence, the specifics of intelligence activities. The developed two tables concentrate and summarise the material on the content of the structural parts of the legislative acts of various countries on intelligence under the title â€œGeneral Provisionsâ€ and the list of key terms included and defined in them. As a scientific hypothesis, the conclusion was formulated that in the near future the countries of regional alliances will develop model laws on intelligence, which will give an impetus for the development of national laws in Ukraine at a new and higher level.